Oral health‐care needs among clients receiving alcohol and other drugs treatment—A scoping review. (18th December 2022) - Poudel, Prakash; Kong, Ariana; Hocking, Stephanie; Whitton, Gilbert; Srinivas, Ravi; Borgnakke, Wenche S.; George, Ajesh
Abstract: Issues: Poor oral health is a significant problem among people who access alcohol and other drugs (AOD) health services, yet little is known about their oral health‐care needs and whether any interventions and guidelines are implemented within AOD treatment services. Approach: A scoping review was conducted to identify scientific literature in three focus areas: oral health knowledge, attitudes and practices of clients and clinicians at AOD‐related services; oral health guidelines for AOD clinicians; and interventions that describe clinicians promoting oral health among clients. Key Findings: Thirty‐two reports were identified. Twenty‐three studies focused on the oral health knowledge, attitudes and practices of AOD clients, but none of the studies explored perspectives of clinicians. Seven clinical practice guidelines were identified but recommendations varied. Only two interventions in which an AOD clinician promoted oral health were identified. Implications: Most reports provided insight into the perspectives of clients accessing AOD treatment services. Little evidence demonstrated that clinical practice guidelines were being implemented into practice, or that oral health promotion was part of the tasks of AOD clinicians. Conclusion: This review identified oral health knowledge gaps and perceived poor attitudes that appeared to be reflected in certain oral health practices among clients. This finding indicates a need to educate clients about oral health while receiving AOD treatment. There was an absence of research about the needs for AOD clinicians to advocate for good oral health, and little evidence exists about effective interventions that could enhance integrating oral health care into AOD treatment services.